2001
DOI: 10.1177/1558925001os-01000207
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Water on Processing and Properties of Thermally Bonded Cotton/Cellulose Acetate Nonwovens

Abstract: Environmentally friendly nonwoven fabrics can be formed through thermal bonding of cotton and cellulose acetate fiber blends at reduced bonding temperature with the aid of a plasticizer. Water has been introduced as an external plasticizer to lower the softening temperature of cellulose acetate fibers and to enhance the tensile strength of cotton/cellulose acetate web. It has been found that water can significantly increase the tensile strength of cotton/cellulose acetate thermally-bonded webs at reasonable bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Because acetone is a flammable solvent there is a preference not to use it in commercial processes, so two alternative methods were further applied for cotton/cellulose acetate nonwovens. 18 Water dip-nip treatment was used instead of acetone solvent pretreatment to make the process more environmentally friendly. It was observed that water could be used as an external plasticizer instead of 20% acetone solvent without compromising web strength and the process is environmentally friendly.…”
Section: Cotton/cellulose Acetate Biodegradable Nonwovensmentioning
confidence: 99%
See 1 more Smart Citation
“…Because acetone is a flammable solvent there is a preference not to use it in commercial processes, so two alternative methods were further applied for cotton/cellulose acetate nonwovens. 18 Water dip-nip treatment was used instead of acetone solvent pretreatment to make the process more environmentally friendly. It was observed that water could be used as an external plasticizer instead of 20% acetone solvent without compromising web strength and the process is environmentally friendly.…”
Section: Cotton/cellulose Acetate Biodegradable Nonwovensmentioning
confidence: 99%
“…Cellulose acetate (CA) fibre was first applied successfully as the binder fibre since it is thermoplastic, hydrophilic and biodegradable. [15][16][17][18] Eastar Bio ® GP copolyester unicomponent and bicomponent (Eastar/PP) fibres were further selected as the binder fibres in recent studies. [19][20][21][22][23] Five different kinds of fibre were used for the study: cotton fibre as the base fibre, and four types of binder fibre, ordinary cellulose acetate (OCA), plasticized cellulose acetate (PCA), Eastar Bio ® copolyester unicomponent (Eastar), and Eastar Bio ® copolyester bicomponent (Eastar/PP) fibres.…”
Section: Cotton and Flax-based Nonwovensmentioning
confidence: 99%
“…[17][18][19][20] The main objective is to have fully biodegradable components in the fiber mixtures, thus producing compostable products. Five different kinds of biodegradable binder fibers were used.…”
Section: Thermal Bondingmentioning
confidence: 99%
“…Cellulose Acetate (CA) fiber has shown to be a good binder fiber for cotton-based biodegradable/compostable thermal calendered nonwoven products by the University of Tennessee, because it is a thermoplastic, hydrophilic and a biodegradable fiber. However, the softening temperature of cellulose acetate fiber is relatively high (Ts: 180-205˚C), even in the presence of some kinds of internal and/or external plasticisers [4,5]. Recently Eastman Chemical Co. developed the "Eastar Bio‚" GP copolyester (Eastar) unicomponent [6] fiber, which can be totally degraded into CO2, H2O and biomass.…”
Section: Introductionmentioning
confidence: 99%